2018
DOI: 10.3390/su10124606
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Social Support and Communities of Practice: Farmer Perceptions of the Challenges and Opportunities of Integrated Crop–Livestock Systems on Organically Managed Farms in the Northern U.S.

Abstract: Most U.S. farms today specialize in either crop or livestock production, failing to harness the potential economic and environmental benefits of integrated crop–livestock systems (ICLS). This specialization is particularly contradictory for organic operations, which aim to promote biodiversity and reduce reliance on outside sources of feed and fertility. This study investigated the challenges and opportunities experienced by farmers interested in integrating crops and livestock on organically managed farms in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 75 publications
1
16
0
Order By: Relevance
“…CoPs are a prominent concept to describe the social and cultural dimensions of innovation and knowledge creation [31]. They are promoted for their ability to support the creation of a shared meaning and collective identity as well as to facilitate social learning processes and the shaping of social practices [23,24,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…CoPs are a prominent concept to describe the social and cultural dimensions of innovation and knowledge creation [31]. They are promoted for their ability to support the creation of a shared meaning and collective identity as well as to facilitate social learning processes and the shaping of social practices [23,24,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…A typical rotation on a US Midwest organic grain farms is maize–soybean–oat ( Avena sativa L.)–alfalfa (Delate et al, 2013), which would have the greatest applicability in an integrated crop‐livestock system, where animal feed and bedding could be derived from the hay and small grain crops in the rotation. However, the feasibility of an organic grain farm incorporating livestock can be limited by labor and economic constraints of mixed crop and livestock operations, even though certified organic regulations emphasize the use of on‐farm sources of fertility (Hayden et al, 2018; USDA AMS NOP, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The herd was part of a crossbreeding program established in 2000, as described by Heins et al [16]. A sociological component of the current study detailed specific obstacles related to integrating crops and livestock as identified by producers over the course of the project, and reported increasing support for integrated crop-livestock systems resulting in growing communities of practice in which farmer-to-farmer knowledge exchange and peer support overcome obstacles to success in these systems [17].…”
Section: Methodsmentioning
confidence: 99%